Refugee protection in Malaysia: a historical and international law perspective within the ASEAN context - Athirah Mohd Anuar,; Nadhilah A. Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2023)
People flee their home countries of origin for a multitude of reasons including fear of persecution, escape from armed conflict and avoiding ethnic cleansing. The factors precipitating large-scale human migration and instances of these exodus can be traced back over several centuries. Regrettably, even in the present era, these occurrences of forced mass migration still persist. This study seeks to examine the historical trajectory of refugee protection in Malaysia, with a specific focus on the legal framework governing the treatment towards refugees within Malaysia’s borders. This is a qualitative legal study harnessing data from online resources including government websites, organizational repositories, case law databases, and academic journals. This study finds that within the ASEAN context, Malaysia and Myanmar have the lowest number of ratified human rights conventions among member states. Further, Malaysia’s adherence to international obligations for refugee protection is contingent upon the enactment of domestic legislation giving effect to its corresponding international instrument. Malaysia’s legal system does not distinguish between illegal immigrants, asylum-seekers or refugees, and case-law evidences differential judgements meted out for the same categories of persons, namely asylum seekers, in Malaysia. The study’s findings will provide valuable insights on the necessity of inter-state cooperation within the ASEAN region, akin to the 1989 Comprehensive Plan of Action for Indo-Chinese Refugees, in addressing the refugee crisis in Malaysia.